Analisis Penggunaan Gadgegt dan Interaksi Sosial Anak Usia Pra Sekolah di Taman Kanak-Kanak Yogyakarta - Fadlilah, Siti; Krisnanto, Paulinus Deny (Jurnal Keperawatan Muhammadiyah, 2019)
Objective: to identify the use of gadget and socialinteraction of preschool age at kindergaten in Yogyakarta.Methods:  The research was conducted at PKK Kindergarten, Maguwoharjo, Sleman Yogyakarta. The research design was Cross Sectional. The study population is the father/mother who has children using gadgets with a sample of 45 respondents using total sampling. Data collection tools are questionnaires. Analysis is done by using Somers'd test.Results:  The most age of respondents was early adulthood, 22 respondents (48.9%). Most of the respondents' education is medium, 27 respondents (60.0%). Most of respondents were housewives, 23 respondents (51.1%). Most the children were 6 years old, 28 children (62.2%). Most of the sexes of children are female, 27 children (60.0%). The use of gadget is medium category, 20 respondents (44.4%). Most of the respondents were good category of social interactions, 32 respondents (71.1%). The results of bivariate analysis between the age of the child, parental education, and parent’s job with the use of gadgets obtained p-value 0.010; 0.024; and 0.003. The results of bivariate analysis between the age of the child, parental education, parent’s job, and the use of gadgets with social interaction obtained p-value 0.028; 0.041; 0.002, and 0.007 Conclusion:  There is a relationship between the age of the child, parental education, and parent’s job with the use of gadgets of preschool children.There is a relationship between the age of the child, parental education, parent’s job, and the use of gadgets with social interaction of preschool children.